Microfluidic systems toward blood hemostasis monitoring and thrombosis diagnosis: From design principles to micro/nano fabrication technologies. Issue 1 (31st January 2022) - Xu, Yi; Yu, Guang; Nie, Ruqiong; Wu, Zhigang
Abstract: Perfusable endothelialized models of microfluidic systems that recapitulate unique biological and biophysical microvasculature conditions are improved with micro/nano engineering advances for monitoring of blood hemostasis and thrombosis treatment. Although bio‐sensors and monitoring devices significantly advance in measuring platelet aggregation and thrombosis kinetics, currently platelet aggregation tests still do not meet the arising clinical requirements. Trying to seek new solutions for such a demanding from clinics, the present review provides an overview of design principles of microfluidic systems and micro/nano fabrication strategies in studying the platelet adhesion and aggregation. We critically sketch the characteristics of microfluidic systems to elucidate the role of platelets in the complex process of thrombus formation. The importance, benefits, and challenges of introduced principles and methods are discussed. The potential from various of basic research to clinical applications is also briefly discussed to help guide designing more versatile point‐of‐care devices for hemostasis monitoring and thrombosis diagnosis and treatment. Abstract : The present review provides an overview of design principles of microfluidic systems and their micro/nano fabrication strategies in studying the platelet adhesion and aggregation. The importance, benefits, and challenges of introduced principles and methods are critically discussed to help guide designing more versatile point‐of‐care (POC) devices for hemostasis monitoring and thrombosis diagnosis and treatment.